Prevalence of mental disorders, psychosocial distress, and perceived need for psychosocial support in cancer patients and their relatives stratified by biopsychosocial factors: rationale, study design, and methods of a prospective multi-center observational cohort study (LUPE study) - Mehnert-Theuerkauf, Anja; Hufeld, Julia Marie; Esser, Peter; Goerling, Ute; Hermann, Myriel; Zimmermann, Tanja; Reuter, Hannah; Ernst, Jochen (Frontiers in Psychology, 2023)
Background: Despite remarkable progress, cancer remains a life-threatening disease for millions of people worldwide, also resulting in significant psychosocial limitations. High-quality, comprehensive cancer care requires patient and family involvement and the provision of needs-based, targeted psychosocial services. Although progress has been made in understanding the occurrence of mental comorbidity and psychosocial distress in cancer patients, comparatively little is known about the course of psychological comorbidity and psychosocial distress in early survivorship among patients and their families. We therefore aim to estimate the prevalence of mental disorders according to the DSM-5, psychosocial distress, perceived needs for psychosocial support and utilization of psychosocial support offers in newly diagnosed cancer patients and their relatives, taking into account potential contributing biopsychosocial factors for the occurrence of psychological comorbidity. Methods/Design: This study follows a prospective multi-center observational cohort design across four measurement time points: within 2 months after cancer diagnosis (t1), and in the follow-up period at 6 months (t2), at 12 months (t3) and at 18 months (t4) after t1. Patients older than 18 years who have a confirmed initial diagnosis of a malignant solid tumor and are scheduled for cancer treatment at one of the participating cancer centers are eligible for study participation. Relatives of eligible patients are also eligible for study participation if they are older than 18 years. Patients are interviewed using the Structured Clinical Interview for DSM-5 Disorders (SCID-5-CV). In addition, patients and relatives receive a set of validated questionnaires at each measurement time point, covering comorbid conditions and functional performance, perceived psychological distress and quality of life, partnership aspects and social relationships, supportive care needs and use of psychosocial support services, health literacy, health behavior and meaning in life. Discussion: This prospective multi-center observational cohort study has a major focus on increasing quality of care and quality of life in cancer survivors through providing rigorous longitudinal data for the development and implementation of target group-specific psychosocial support services.